Т. 1; Энергетика: эффективность, надежность, безопасность - Литвак В. В. Валерий Владимирович; Кузнецов Г. В. Гений Владимирович; Панин В. Ф. Владимир Филиппович; Сечин А. И. Александр Иванович (2013, 2013)
Заглавие с титульного экрана